THE REFLECTIONS ON THE HISTORICAL DEVELOPMENT OF INTERNATIONAL LAW OF WAR - SZCZUREK Tadeusz (2011)
The article discusses the international law of armed conflicts and international humanitarian law. The way of presenting these issues took the form of a chronological presentation of selected historical events and a short summary of the relevant - in the author's opinion - legal agreements related to them. The text can be divided into two parts describing separate but interrelated issues. The first part deals with the issue of the law of war - its origins, historical evolution and the motives for introducing it into social relations. The issues of the knightly ethos as the source of the modern European idea of ​​a just war requiring moral justification were also raised. The second part of the article deals with humanitarianism in times of war and its legal placement in international regulations, especially in the Hague Conventions. The obligations and orders applied to states and governments in terms of introducing and applying regulations of international humanitarian law were indicated.